Comparative Anti-Cancer and Anti-Inflammatory Activities of Essential Oils from the Bark and Flower of Magnolia officinalis Rehd. et Wils - Ke-Xin Hao; Yun-Fang Hao; Jie Zhang; Xi-Lin Xu; Jian-Guo Jiang (Foods, 2024)
This study was designed to compare the antioxidant, antitumor and anti-inflammatory effects of essential oils from the bark and flower of Magnolia officinalis Rehd. et Wils. Distillation extraction and steam distillation were used to extract EOs from the bark and flower. The results showed that the contents of EOs of SDE-F and SDE-B were much higher than that of SD-F and SD-B. EOs from the bark were rich in eudesmol (especially α-eudesmol) and exhibited a stronger antioxidant effect than the flower. The anti-tumor effects of SD-B and SD-F on HepG2 and MDA-MB-231 cells were better than that of SDE-B and SDE-F. The inhibitory rates of SD-B and SD-F on MDA-MB-231 cells were 59.21% and 48.27%, exceeding that of positive control 5-fluorouracil (47.04%) at 50 μg/mL. All four EOs exhibited excellent anti-inflammatory activities through the regulation of nitric oxide production and pro-inflammation cytokines in LPS-induced RAW 264.7 cells and they also remarkably suppressed the mRNA expressions of nitric oxide synthase, IL-6 and TNF-α at the concentration higher than that of positive control dexamethasone. These results indicated significant differences in the composition, and anti-inflammatory and anti-tumor activities of EOs extracted by different methods and provided a theoretical basis for their development and utilization.